DAYA TERIMA BERAS ANALOG DARI TEPUNG UBI KAYU SEBAGAI PANGAN POKOK DI DESA TANJUNG BERINGIN KECAMATAN SUMBUL KABUPATEN DAIRI TAHUN 2014 - christi gestarini; Evawany Y Aritonang; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Indonesia is the country with the highest rice consumption reached 139 kg/capita/year in 2013. The consumption is not supported by appropriate rice production, so the government import rice from other countries. In addition, the government has also been implementing diversification program for the utilization of local food, including cassava. Desa Tanjung Beringin produce cassava but underutilized because accustomed to eating rice. This research is an experimental research that is making analog rice using cassava flour with the addition of water. Panelists in this research are women in the village of Tanjung Beringin as many as 30 people. Acceptability test results obtained with organoleptic and was analyzed descriptively. The value of nutrient content adjusted to DKBM. The results of this study indicate that the acceptance of women in the village of Tanjung Beringin to analog rice is low. It is seen from the percentage of rice taste assessment analog only 47.778% and categorized dislikes. The color rice is less liked by the percentage rating of 63.333%. Aroma and texture of rice analog liked category by their respective percentages of 80% and 78.889%. Based DKBM, comparison of the quantity of nutrients contained in the rice and rice analogue of cassava flour is almost same. Both of the rice and analog rice contain of carbohydrates, phosphor and calcium and they produce nearly the same energy. So have suggested the addition of the composition to improve the flavor and color of rice analog and enrichment nutritional content and need to be developed a diversification program of cassava that can be accepted by society.